Competence of Public Health Center Health Extension Officers in the Tual City Health Service Work Area - Diana (Journal of Public Health and Pharmacy)
This research aims to determine health promotion competency through the abilities, attitudes, and skills of Community Health Center extension officers in the work area of the Tual City Health Service. This research is qualitative research with a case study approach. There were 13 informants with the criteria as holders of the Promkes Program at the Community Health Center. Data collection techniques use in-depth interviews and activity documentation. The research results show that the officers' abilities regarding health promotion, competence, strategies, methods, and media use are still based on experience because the professionalism of extension officers has not been standardized. Officers' efforts still need to meet national standard health promotion coverage. The attitude of officers needs to be improved because it is hampered by the lack of supporting facilities and infrastructure for counseling and the monotonous creativity of officers due to lack of training. Officers' skills in using media are adequate, although still limited to print media and cross-sector collaboration. Difficulty accessing transportation and lighting equipment (electricity), especially at community health centers located on islands, is the cause of hampered health education.